Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18203/2349-3933.ijam20170087
|View full text |Cite
|
Sign up to set email alerts
|

To study the incidence of gestational diabetes mellitus and risk factors associated with GDM

Abstract: Background: Diabetes is estimated to complicate 2-5% of all pregnancies of which 90% of those are detected during pregnancy i.e. gestational diabetes mellitus (GDM) and the rest are overt or pregestational i.e. either Type 1 or Type 2. According to ADA, approximately 7% of all pregnancies are complicated by GDM resulting in more than 2,00,000 cases annually. The aim was to study the incidence of GDM among pregnant women between 24 to 28 weeks of gestation, to evaluate and compare the occurrence of risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
(1 reference statement)
0
8
0
Order By: Relevance
“…Studies conducted in other parts of India have documented similar observation thus making family history of DM an important variable in the etiology of GDM. 3,4,9,10 The present study revealed that risk factors associated with obstetric history such as past history of GDM (23.8%), history of macrosomia in previous pregnancy (2.1%) and Bad Obstetric History (4.2%) were more common in GDM than non-GDM group; however, amongst all these variables only past history of GDM was found to be significantly associated with GDM. Varija Thathagari et al, Shridevi AS et al and Kalpana Varma et al found all these three risk factors associated with previous pregnancy to be statistically significant determinants for developing GDM.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Studies conducted in other parts of India have documented similar observation thus making family history of DM an important variable in the etiology of GDM. 3,4,9,10 The present study revealed that risk factors associated with obstetric history such as past history of GDM (23.8%), history of macrosomia in previous pregnancy (2.1%) and Bad Obstetric History (4.2%) were more common in GDM than non-GDM group; however, amongst all these variables only past history of GDM was found to be significantly associated with GDM. Varija Thathagari et al, Shridevi AS et al and Kalpana Varma et al found all these three risk factors associated with previous pregnancy to be statistically significant determinants for developing GDM.…”
Section: Discussionmentioning
confidence: 49%
“…Varija Thathagari et al, Shridevi AS et al, Maxima Anand et al and Kalpana Varma et al also reported that advancing maternal age is a significant risk factor for developing GDM. 3,4,9,10 However Pallav Parikh et al in Gujarat did not observe such a significant finding. 11 This may be due to disparity in the study design with limitation to rural population in Gujarat.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…GDM refers to a varying degree of impaired glucose tolerance occurring for the first time during pregnancy, excluding patients who were with diabetes previous to gestation but were first diagnosed during pregnancy [1]. In China, the incidence of GDM is about 5%–7%, and there is an increasing trend [22]. According to the results of traditional research methods, the etiology of GDM is closely related to insulin resistance.…”
Section: Discussionmentioning
confidence: 99%